APLIKASI GROSIR BAJU BERBASIS WEB MENGGUNAKAN METODE APRIORI DI TOKO GROSIR ANNUR - Ulum, Bahrul; Putra Eka Prismana, IGL Putra Eka Prismana; Augusta Jaannatul Firadusi, Reza (Inovate, 2024)
In technology era a company must have an information system that functions as a producer of information for management. Inside the store always need a system to collect, store and distribute information. The database design planning for this website uses a database application program, namely MySQL, which is an integrated application system. Inside there is a database engine, interface, data manager, and programming system that can make database applications made according to needs. This website design consists of several elements, namely text, images, materials and research materials which are created and processed using the Dreamweaver application program, Microsoft Word 2010, Adobe Photoshop CS3 and using the MySQL database. The results of this final project research are that the Application of Apriori at the Gosir Annur Store can assist in managing sales data. Besides that, it can provide information to people who want to have products owned by Annur Grocery Stores, without having to come directly to the seller. By accessing the Internet, information will be received quickly, saving costs and time. Keywords: Information System, Javascipt, Online, MySQL, Computer